Liquid phase oxidation chemistry in continuous-flow microreactors. (23rd July 2015) - Gemoets, Hannes P. L.; Su, Yuanhai; Shang, Minjing; Hessel, Volker; Luque, Rafael; Noël, Timothy
Abstract : This review gives an exhaustive overview of the engineering principles, safety aspects and chemistry associated with liquid phase oxidation in continuous-flow microreactors. Abstract : Continuous-flow liquid phase oxidation chemistry in microreactors receives a lot of attention as the reactor provides enhanced heat and mass transfer characteristics, safe use of hazardous oxidants, high interfacial areas, and scale-up potential. In this review, an up-to-date overview of both technological and chemical aspects of liquid phase oxidation chemistry in continuous-flow microreactors is given. A description of mass and heat transfer phenomena is provided and fundamental principles are deduced which can be used to make a judicious choice for a suitable reactor. In addition, the safety aspects of continuous-flow technology are discussed. Next, oxidation chemistry in flow is discussed, including the use of oxygen, hydrogen peroxide, ozone and other oxidants in flow. Finally, the scale-up potential for continuous-flow reactors is described.